2022
DOI: 10.18178/ijiet.2022.12.6.1652
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Transactional Distance Theory in e-Learning Environment during COVID-19: Perspective from Computer Science Students

Abstract: This study is based on the separation of teachers and learners caused by the COVID-19 pandemic, and the implication of Moore’s Transactional Distance Theory, which proliferated for nearly 30 years but has been inconsistently validated empirically. The quantitative approach was employed, with questionnaires distributed based on the learners’ perspectives. The subjects of the study include 153 respondents from computer science department of an Indonesian public university. Three key tenets of transactional dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Similar to previous studies conducted during the pandemic (Batita & Chen, 2022; Sevnarayan, 2022), the current research revealed that both TDT and CLT emphasize the significance of learner autonomy and social context in the learning process. The findings reveal that teachers provided limited guidance to create autonomous learners.…”
Section: Discussion Recommendations and Limitationssupporting
confidence: 86%
“…Similar to previous studies conducted during the pandemic (Batita & Chen, 2022; Sevnarayan, 2022), the current research revealed that both TDT and CLT emphasize the significance of learner autonomy and social context in the learning process. The findings reveal that teachers provided limited guidance to create autonomous learners.…”
Section: Discussion Recommendations and Limitationssupporting
confidence: 86%
“…Both male and female students' perceptions of the TD were not high. Similarly, there are studies in which gender does not pose a significant difference (Bayır & Mahiroğlu, 2017;Batita & Chen, 2022;Bolliger ve Halupa, 2018;Horzum, 2011;Horzum, 2015;Huang et al, 2016;Karakuş & Yanpar-Yelken 2020;Lenear 2006;Rabinovich, 2009;Üstün, 2021;Vasiloudis et al ,2015). According to Gavrilis et al (2020), on the other hand, men's perceptions of transactional distance are lower.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 99%
“…As a result of the study, the importance of TD in increasing learner participation was emphasized. Batita & Chen (2022), in their study, examined students' transactional distance perceptions. At the end of the study, tarnsactional distance perceptions were refined in terms of dialogue, structure, and learner autonomy and it was determined that age, gender, and program of study had no effect on operational distance perception.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can offer benefits such as improved collaboration, engagement, and student autonomy [6][7][8]. However, teachers also face challenges such as acquiring technical skills [9,10], preparing digital teaching resources, and managing potential student distractions [11,12]. The integration of e-learning into traditional educational environments can offer numerous benefits, Teachers are responsible for guiding students through digital programs, using educational tools and technologies to enhance the learning experience.…”
Section: Introductionmentioning
confidence: 99%